2023
DOI: 10.1007/s10339-023-01126-4
|View full text |Cite
|
Sign up to set email alerts
|

Remembering to whom we transmit information during pandemics: the effect of face masks on destination memory

Abstract: Considering the global pandemic we currently experience, face masks have become standard in our daily routine. Even though surgical masks are established as a safety measure against the dissemination of COVID-19, previous research showed that their wearing compromises face recognition. Consequently, the capacity to remember to whom we transmit information—destination memory—could also be compromised. In our study, through a between-participants design (experiment 1) and a within-participants design (experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Impairments in social cognition in TBI have also been reported by research on destination memory. Destination memory refers to the ability to remember to whom a piece of information was previously transmitted [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Research has demonstrated a decline in destination memory in TBI, which was found to be related to the ability to represent, conceptualize, and reason about others’ mental states [ 11 , 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairments in social cognition in TBI have also been reported by research on destination memory. Destination memory refers to the ability to remember to whom a piece of information was previously transmitted [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Research has demonstrated a decline in destination memory in TBI, which was found to be related to the ability to represent, conceptualize, and reason about others’ mental states [ 11 , 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in social cognition in TBI have also been reported by research on destination memory. Destination memory refers to the ability to remember to whom a piece of information was previously transmitted [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Research has demonstrated a decline in destination memory in TBI, which was found Brain Sci.…”
Section: Introductionmentioning
confidence: 99%